Evaluation of a Patient Education Game Design Activity - Andrea Porter; Olivia Kim; Olufunmilola Abraham (University of Minnesota Libraries Publishing, 2023)
Background: Game-based learning has been used in pharmacy education settings with the instructor developing a game for students to play to enhance learning. However, there is a paucity of data about health sciences students designing a game themselves to further their understanding of a complex topic. The purpose of this study was to describe and assess a game design activity focused on patient education of anticoagulants in a pharmacotherapy skills laboratory setting. Innovation: Second-year pharmacy students enrolled in a pharmacotherapy skills laboratory course worked in teams in a one-hour active learning activity to design a game intended to educate patients about their medication. A pre/post analysis of student attitudes about game-based learning and the activity, as well as knowledge, was conducted. Findings: The large majority of students (80.5%) agreed that the activity was an effective way to develop patient education strategies. Through the survey and free-response questions, students reported that the game design activity facilitated positive group collaboration and allowed students to take the perspective of their patients. Students also requested additional time to complete the activity. Knowledge assessment scores of key patient education points increased from 66.5% prior to the activity to 71.5% one week following the activity (p<0.05).  Conclusion: The game design activity served as a novel teaching method for pharmacy students to actively learn about anticoagulant medications while developing an innovative patient education strategy. Although there was an increase in knowledge scores, students highlighted the impact on group collaboration and taking the perspective of their patients.